Press, literature and politics during the first romanticism: literary criticism and liberal thought in France (1815-1830) - Anjos, Yuri Cerqueira dos [UNESP] (Univ Fed Minas Gerais, Dept Filosofia & Ciencias Humanas, 2016)
In the field of literary history of early French Romanticism, the opposition between liberal's classicism and royalist's romanticism is a fundamental theme. Critics have often interpreted this situation as a misunderstanding where those who advocated for freedom in politics were conservative in literature and vice versa. However, it is possible to consider more deeply the links between political liberalism and literary classicism in France. To do this, we focus in this article on the liberal press of the Restoration (1815-1830), notably on the leading daily Le Constitutionnel. This material allows us to dissect the multiple meanings of the word freedom, polysemy that seems to be at the core of the diversity of political and literary perspectives of the time. More than a simple oddity, the liberal classicism proves to be a coherent posture. Through this analysis we will be able to have a better understanding of the powerful resistance against romanticism in the early years of this movement in France.
Keywords: liberalism; French romanticism; press; freedom